Common law rights and liabilities in relationship debt - Ab Rahman, Suhaimi (American - Eurasian Network for Scientific Information, 2013)
Relationship debt is a term usually used to describe a situation where a woman becomes liable for the debt of her spouse or partner. This occurs when she becomes the guarantor for her partner's loan or when she is co-borrowing with her partner. She becomes liable for the whole loan when her partner fails to meet the loan. Most of the time, woman will signed the loan agreement without acknowledging the legal and financial obligation. She signed it purely on a basis of relationship of dependence and emotional ties that exist between the woman and her partner. Is there a legal protection for them? This is a review paper on the common law position towards these women in the United Kingdom, Australia and Malaysia. It explores on the legal mechanism for which this woman can argue in the court of law so as to avoid being liable for her partner's debt.